Fabulous monsters : Dracula, Alice, Superman, and other literary friends - Manguel, Alberto (Yale University Press, 2019)
An original look at how literary characters can transcend their books to guide our lives, by one of the world's most eminent bibliophiles Alberto Manguel, in a style both charming and erudite, examines how literary characters live with us from childhood on. Throughout the years, they change their identities and emerge from behind their stories to teach us about the complexities of love, loss, and the world itself. Manguel's favorite characters include Jim from Huckleberry Finn, Phoebe from The Catcher in the Rye, Job and Jonah from the Bible, Little Red Riding Hood and Captain Nemo, Hamlet's mother, and Dr. Frankenstein's maligned Monster. Sharing his unique powers as a reader, Manguel encourages us to establish our own literary relationships. An intimate preface and Manguel's own "doodles" complete this delightful and magical book.